Enhancing Counsellors' Resilience - Abdullah, Haslee Sharil Lim; Mohd Noah, Sidek (INTI Publishing House Sdn Bhd, 2005)
Counselling is a process that flows in two directions obviously influencing not only the client but also affecting the personal life of the counsellor. The impact can be for better or for worse, making the counselling profession one of the most spiritually fulfilling as well as emotionally most draining occupations. Some counsellors flourish as a result of their work by learning from those they try to help. On the other hand, some counsellors become exhausted and despondent. This paper will focus on what has gone right with those counsellors who succeed despite the odds stacked against them. What do they have in them to persist after encountering setbacks and disappointments? Exploration will enable counsellors to check their resiliency level and emulate ways to enhance it.